Efectos de la aplicación de Bioestimulantes en el pasto janeiro (Erioclhoa polystachya) en la zona de Babahoyo” - Zarate Rivas, Jugling Dayanara (2020)
Pastures and forages are the most widely distributed plants in the world and constitute the main source of food for domestic and wild herbivores that graze in grasslands, with proper management they can provide the necessary nutrients and develop their physiological functions. The problems that normally occur in grasslands are mostly due to the affected use of pastures and the lack of adequate productive parameters such as: altitude, rainfall, nutrients and the use of species with low yield potential, which leads to limited forage production, reducing the amounts of dry matter per square meter of cultivated area. Fertilization in pastures constitutes the factor that specifically affects crop yields; It is possible to use complementary mineral products such as biostimulants or biofertilizers that optimize the physiological functions of plants, contributing significantly to crop yield. This study applied different biostimulants in varied doses, obtaining favorable results in the length of the leaf with the Yoduo biostimulant in a dose of 1L / ha reaching a measure of 28.25 cm, in addition with the same treatment positive results were obtained regarding the Green and dry matter weight. It is concluded that the effect of biostimulants in Pasto de Janeiro has the potential to increase the production and current competitiveness of this crop.